Health Belt sebagai Ikat Pinggang Terapi Reumatik - Rachma Azkia Zahra; Adi Wicaksana; Wiwin Novianti; Mohammad Ananda Reza Kurniawan; Indica Yona Okyranida (UNIVERSITAS INDRAPRASTA PGRI, 2021)
Rheumatism is sometimes unnoticed by the public. The most common symptom is pain. The surprise that people do when they feel these symptoms is to buy medicines to relieve pain. These medicines are not necessarily suitable and safe because of the state of pain is not yet known the exact cause. The adverse effects of rheumatic conditions are disability, resulting in huge health care costs and job loss. In the manufacture of belt products used that are large in order to store a series of Arduino that will program rheumatic therapy. In the development of this tool in addition to using the Arduino kotrol system as its operating module also uses a vibrating system produced by the rotation of the electric motor. The electric motor used is a low-power DC motor with a low rotation, To connect the DC motor with the control system using relays and transistors in order to regulate the work of the motor, the relay function as a circuit breaker when the time has been reached so that the motor rotation must be stopped. To see the time display and operation of the equipment can be seen on the monitor that uses an LCD with 2x16 characters.